Adjustment of the methodological guidelines for establishing the permitted surface water abstraction and environmental flow for freshwater ecosystem conservation - Valentina G. Dubinina; Aleksey E. Kosolapov; Nikolay I. Koronkevich; Oksana I. Nikitina; Mikhail S. Chebanov (Водное хозяйство России: проблемы, технологии, управление)
Spatial and temporal variability of river runoff determines habitat conditions for aquatic and semi-aquatic species of fl ora and fauna. Due to the massive anthropogenic impact on water bodies, establishing sound norms of permitted surface water withdrawal and environmental fl ow is becoming an increasingly important task for freshwater ecosystem conservation and restoration. Th e article describes the methodology for standardizing permitted surface water withdrawal and determining the environmental fl ow (release) and information on the methodology adjustment.